1979
DOI: 10.1029/ja084ia11p06524
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between auroral particle distributions and magnetic field perturbations associated with field‐aligned currents

Abstract: Simultaneous measurements of magnetic fields and soft particle distributions in the topside auroral ionosphere reveal the relationships between field‐aligned currents and primary and secondary auroral particles. In the evening MLT sector the region 2 field‐aligned currents, which are directed into the ionosphere, are found to extend on the average 2.4° of invariant latitude equatorward of the low‐latitude boundary of 1‐keV electron precipitation from the magnetospheric plasma sheet. This current system is foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
37
1

Year Published

1980
1980
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 27 publications
7
37
1
Order By: Relevance
“…Klumpar (1979) found that R2 FACs extend on average 2.4 • equatorward of the electron-precipitation boundary. Gussenhoven et al (1983) reported that the ion-precipitation boundary is 1.4 • equatorward of the electron boundary, the separation often reaches up to 3 and even 5 • in latitude.…”
Section: Relative Positionsmentioning
confidence: 95%
“…Klumpar (1979) found that R2 FACs extend on average 2.4 • equatorward of the electron-precipitation boundary. Gussenhoven et al (1983) reported that the ion-precipitation boundary is 1.4 • equatorward of the electron boundary, the separation often reaches up to 3 and even 5 • in latitude.…”
Section: Relative Positionsmentioning
confidence: 95%
“…These ions show a pitch angle distribution with a relative minimum in the upward direction (~ ~ 180 ~ in the northern hemisphere and e ~ 0 ~ in the southern hemisphere) and with a relative maximum at an intermediate pitch angle in the upward hemisphere, thus forming an upflowing cone in velocity space, such as shown in Figure 9b. These are sometimes referred to as conics (from the shape of the velocity space distribution such as Figure 9b) and sometimes referred to as transversely accelerated ions (TAI) (Klumpar, 1979). Conical distributions have been observed at altitudes as low as 400 km (Whalen et aL, 1978) and up to at least 8000 km (Sharp et al, 1977;Ghielmetti et aL, 1978;Klumpar, 1979;Fennell etal., 1979;Gorney etal., 1981).…”
Section: B Ion Distributionsmentioning
confidence: 99%
“…These are sometimes referred to as conics (from the shape of the velocity space distribution such as Figure 9b) and sometimes referred to as transversely accelerated ions (TAI) (Klumpar, 1979). Conical distributions have been observed at altitudes as low as 400 km (Whalen et aL, 1978) and up to at least 8000 km (Sharp et al, 1977;Ghielmetti et aL, 1978;Klumpar, 1979;Fennell etal., 1979;Gorney etal., 1981).…”
Section: B Ion Distributionsmentioning
confidence: 99%
“…Numerous papers have been written on this subject since then, using particle flux measurements or optical observations of the aurora and the field-aligned current data deduced from magnetic field measurements or from incoherent scatter radar observations (e.g., Klumpar, 1979;Burke et al, 1980;Robinson et al, 1982;Senior et al, 1982).…”
Section: Introductionmentioning
confidence: 99%